Water and public policy in India : politics, rights, and governance - Acharya, Deepti (New York : Routledge, 2022)
"This book explores the conceptual and theoretical frameworks of Right to Water and analyzes its values in the context of water policy frameworks of the union governments in India. It uses a qualitative approach and combines critical hermeneutics with critical content analysis to introduce a new water policy framework. The volume maps the complex argumentative narrations which have emerged and evolved in the idea of Right to Water and traces the various contours and the nature of water policy texts in independent India. The book argues that the idea of Right to Water has emerged, evolved and is being argued through theoretical arguments and is shaped with the help of institutional arrangements developed at the international, regional, and national levels. Finally, the book underlines that India's national water policies drafted respectively in 1987, 2002 and 2012, are ideal but are not embracing the values and elements of Right to Water. The volume will be of critical importance to scholars and researchers of public policy, environment, especially water policy, law, and South Asian studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Water-supply -- Government policy -- India; Right to water -- India; Human rights -- India; POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / Public Policy / Environmental Policy; SOCIAL SCIENCE / General